ANALISA DAMPAK PENGEMBANGAN DESTINASI WISATA BAHARI PULAU ABANG TERHADAP MASYARAKAT - Hendra Syaiful; Eva Amalia; I Nyoman Budiartha (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2023)
Pulau Abang which is located on Batam Island, Riau Archipelago Province, is now popular as a marine-based tourist destination. The development of tourism which is very rapid and concentrated will possibly having various impacts namely . economic, socio-cultural and environmental impacts This study aims to elaborate and analyze the positive and negative impacts of these aspects. . Impact analysis will provide an overview of how a destination affects towards the society. This research uses a qualitative descriptive method which will become an identification step for further collaborative development strategies that can optimize the improvement of people's welfare and impacted to the tourism sector.